2009
DOI: 10.1007/s10646-009-0432-0
|View full text |Cite
|
Sign up to set email alerts
|

Sea urchin embryos as an in vivo model for the assessment of manganese toxicity: developmental and stress response effects

Abstract: In the marine environment increasing concentrations of bio-available compounds often result from anthropogenic activities. Among metal ions, manganese represents a new emergent factor in environmental contamination. Here, we studied the effects of manganese on Paracentrotus lividus sea urchin embryos using biological and biochemical approaches for the analysis of impact on development, tissue accumulation and stress markers. Embryos were continuously exposed from fertilization to manganese at concentrations ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
46
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(52 citation statements)
references
References 44 publications
6
46
0
Order By: Relevance
“…We demonstrated that embryos showed an elevated tolerance/resistance to Mn, as they accumulated high amounts into cells in a time-and concentration-dependent manner without producing lethal effects. Rather, we observed a concentration-dependent increase in the number of morphological abnormalities and in the levels of the hsc70 and hsc60 proteins (Pinsino et al, 2010). In addition, we found that the exposure to the highest Mn concentration tested (61.6 mg l À1 or 1.12 mM) prevents skeleton growth which result in spicule-lacking embryos, interferes with calcium uptake and internalization into cells, and causes remarkable consequences in skeletogenic gene expression and ERK mediated signaling pathway (Pinsino et al, 2011).…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations
“…We demonstrated that embryos showed an elevated tolerance/resistance to Mn, as they accumulated high amounts into cells in a time-and concentration-dependent manner without producing lethal effects. Rather, we observed a concentration-dependent increase in the number of morphological abnormalities and in the levels of the hsc70 and hsc60 proteins (Pinsino et al, 2010). In addition, we found that the exposure to the highest Mn concentration tested (61.6 mg l À1 or 1.12 mM) prevents skeleton growth which result in spicule-lacking embryos, interferes with calcium uptake and internalization into cells, and causes remarkable consequences in skeletogenic gene expression and ERK mediated signaling pathway (Pinsino et al, 2011).…”
Section: Introductionmentioning
confidence: 72%
“…We found that P. lividus embryos accumulate high amounts of Mn in a concentration-and time-dependent manner. Its accumulation was also directly correlated with a concentration-dependent increase in the number of morphological abnormalities (Pinsino et al, 2010). As the highest Mn concentration used (61.6 mg l…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…We addressed this gap in knowledge in an investigation of the effects of Gd on the development of sea urchin embryos and larvae. The sea urchin embryo has long been an important model organism in developmental biology and eco-toxicology to assess the hazard posed by contaminants entering the marine environment (Radenac et al, 2001;Russo et al, 2003;Roccheri et al, 2004;Pinsino et al, 2010;Tellis et al, 2014). A wealth of research with sea urchin embryos and larvae have shown that chemical pollutants impair development and that the larval skeleton is a particularly vulnerable response variable for ecotoxicological tests (Bonaventura et al, 2015;Morroni et al, 2016).…”
Section: Introductionmentioning
confidence: 99%